Modelling and Simulation for Small Signal Stability of Multi-machine Power System under Various Disturbance Conditions - Ohnmar Swe; Soe Win; Zarchi Linn (Department of Electrical Engineering ITS and FORTEI, 2020)
This paper presents the small signal stability of multi-machine power system over the 58-Bus, 26-Machine, Yangon Distribution Network and is validated with MATLAB software under various disturbance conditions. Time-domain solution analysis is employed to determine the small signal dynamic behavior of test system. Transtability model is used to perform time-domain simulation in SIMULINK. The simulation is carried out for normal condition, reference voltage of regulator (Vref) disturbance, mechanical torque (Tm)disturbance and network (fault) disturbance and the conditions of change in center of inertia for rotor angle (delta COI), slip for center of inertia (slip COI), field current and mechanical torque are observed. According to the simulation results, perturbation of Vref shows only instability on the system. But ramping of Tm and network disturbance can cause large disturbance on the system and unstable conditions can be observed.Keywords: load flow, multi-machine power system, small signal stability analysis,system disturbances, time domain simulation.